The Opinions and Attitudes of Local People In terms of Government Trust, Knowledge, Transparency and Corruption in International Festivals: International Antalya Film Festival Example - AKSU, AKIN; ARSLAN, SELİN; YARDIMCI, EYLEM OLCAY; ERKAYA, BERİL (Turizam, 2020)
Festivals which were celebrated by communities, can be seen under the name of MICE term. The present study aimed to measure the opinions and attitudes of local people in Antalya about the International Antalya Film Festival under the components of impact level, trust in the organizing committee, trust in the government, corruption and transparency. The study was conducted in July of 2019 in the districts of Lara, Konyaaltı, Kundu, Serik, Kemer and Kepez in Antalya city of Turkey. According to ANOVA and t test results, it was concluded that only education caused a significant difference in the participants’ interest in the International Antalya Film Festival. In addition to this, it is concluded that the participants have issues of trust related to the organizing committee and the government and the fairness and transparency of the management processes. Apart from the answers given to the measurement tool, several participants verbally stated that the locals were not adequately informed about the festival and they could not easily participate in the film festival.